Factors Influencing Mosquito Nest Eradication in Dengue Hemorrhagic Fever Prevention - Siregar, Deborah; Harefa, Lenny; Uma, Milka Rambu Andu (Universitas Pelita Harapan, 2025)
Dengue hemorrhagic fever (DHF) poses a significant public health in Indonesia. Despite government efforts to control disease vectors, the rising population density and mobility in Tangerang Regency have contributed to the rapid spread of DHF. This highlights the urgent need to eradicate mosquito nests for outbreak management and prevention. This study aims to identify risk factors associated with mosquito nest eradication in the Tangerang Regency. A cross-sectional design was used, with 400 participants selected through convenience sampling. Data were analyzed using logistic regression. The results of the multivariate analysis revealed age (p-value = 0.012), knowledge (p-value = 0.001), and support from healthcare workers (p-value = 0.003) as variables linked to mosquito nests eradication. Knowledge was the most dominant variable (OR = 5.857); individuals with low knowledge levels were 5.8 times less likely to engage in mosquito nest eradication compared to those with high knowledge after being controlled for age and support from health workers. These findings underscore the urgency of addressing these risk factors. Nurses can play a key role by providing health education to the community, emphasizing the importance of regularly draining and cleaning water containers, covering water storage, and reusing or recycling waste to reduce mosquito breeding sites.